Data analysis of the internal background measurements of 40Ca100MoO4 scintillation crystals - N. D. Khanbekov; V. V. Alenkov; A. A. Burenkov; O. A. Buzanov; V. N. Kornoukhov (Ядерна фізика та енергетика)
The sensitivity of neutrinoless double beta (02) decay experiments is mainly dependent on the internal background of a detector which, in its turn, is defined by the purity of material and possibility for selection of background events. The AMoRE (Advanced Mo based Rare process Experiment) collaboration plans to use 40Ca100MoO4 scintillation crystals as a detector for search of 02 decay of 100Mo isotope. A purpose of this pa-per is further investigation of internal background of 40Ca100MoO4 scintillation elements with a low background setup at YangYang underground laboratory. We present new approaches for selection of background events from analyzing data and the latest updated values of background index of 40Ca100MoO4 crystals as a result of the new technique application.